Strain Hardening Properties of Polymeric Materials for Artificial Blood Vessels - A Research Study Investigating the Strain Hardening Properties of Alginate and Xanthan Gum - Hjalmarsdottir, Hekla; Nilsson, Kristina (My University, 2020)
Biomaterials and artificial body tissues are a part of life science and a field where there is always room for new inventions and improvement. Previous research shows that viscoelastic properties like strain hardening are important to consider in order to develop artificial body tissue. Therefore, this research study investigates the strain hardening properties of hydrogels based on the polysaccharides alginate and xanthan gum. The investigation was conducted by examining the polysaccharides rheologically in small and large amplitude oscillatory shear. The results indicate that both alginate and xanthan gum start showing strain hardening behavior at high strain (10%-100%). Therefore it can be suitable for future artificial soft body tissue engineering. Alginate was tested with ionoprinting as well to see if it is possible to insert local stiffness in polysaccharides, which the study concludes is possible. A lesson plan for a laboratory session in Swedish upper secondary school was developed to increase public engagement and knowledge of viscoelasticity and strain hardening properties.
Keywords: Alginate; biomaterial; hydrogel; ionoprinting; polymer; rheology; strain hardening; viscoelasticity; xanthan gum